A physical model-based approach to detecting sky in photographic images - Jiebo Luo; Etz, S.P. (IEEE transactions on image processing, 2002)
Sky is among the most important subject matter frequently seen in photographic images. We propose a model-based approach consisting of color classification, region extraction, and physics-motivated sky signature validation. First, the color classification is performed by a multilayer backpropagation neural network trained in a bootstrapping fashion to generate a belief map of sky color. Next, the region extraction algorithm automatically determines an appropriate threshold for the sky color belief map and extracts connected components. Finally, the sky signature validation algorithm determines the orientation of a candidate sky region, classifies one-dimensional (1-D) traces within the region based on a physics-motivated model, and computes the sky belief of the region by the percentage of traces that fit the physics-based sky trace model. A small-scale, yet rigorous test has been conducted to evaluate the algorithm performance. With approximately half of the images containing blue sky regions, the detection rate is 96% with a false positive rate of 2% on a per image basis.